Analisis Kadar Air, Susut Bobot, dan Warna (L*, a*, dan b*) pada Paprika Hijau (Capsicum annuum var Grossum) dengan Jenis Edible Coating Berbeda - Amelia Amelia; Kusumiyati Kusumiyati; Farida Farida (Paspalum: Jurnal Ilmiah Pertanian, 2023)
Paprika (Capsicum annuum var Grossum) is a prospective horticultural commodity to be developed in Indonesia, so the production needs to be increased. However, paprika is included as a perishable commodity, so it affects the quality and shelf life. Postharvest technology that can maintain quality and extend the shelf life of horticultural products is edible coating. Gelatin and chitosan are materials that can be used as coatings. The experiment aimed to determine the effect of edible coating types on the quality of green peppers in the form of water content, weight loss, and color components (Lightness, a*, and b*). This experiment was carried out from October 2022 to March 2023 at the Horticulture Laboratory, Faculty of Agriculture, Universitas Padjadjaran. The experiment used a completely randomized design consisting of 6 treatments, namely control (without edible coating) stored 0 days, control (without edible coating), 5% Gelatin, 10% Gelatin, 1% Chitosan, and 2% Chitosan stored 8 days and repeated 4 times. The results showed that there was an effect of edible coating on the moisture content and weight loss of the peppers, but did not affect the color components in the form of Lightness (L*), a*, and b*. Chitosan 2% could maintain the moisture content of green peppers during storage for 8 days, while treatment with 5% gelatin and 2% chitosan resulted in lower weight loss compared to the control.